Um Método Espectrofotométrico para Quantificação de Furfural em Cachaças por Extração Líquido-Líquido - Mélo, Erika Maria Gouveia de (2014)
A simple and rapid method for determination of furfural in yeast-distilled beverages from sugar cane by liquid-liquid extraction (LLE) is proposed. The techniques of extraction and / or preconcentration allows analytes can be determined by separation of sample components due, mainly, the solubility differences that allows the separation of one or more matrix components by contact and mechanical stirring of a solvent immiscible or slightly miscible in the matrix. The component to be separated (analyte) must be soluble in this solvent. In the proposed method equal amounts of standard sample and chloroform are mixed, the mixture is stirred mechanically for about 2 minutes, forming an emulsion. After this, it´s expected one minute to complete phase separation. Once the analyte is in the extractor solvent (chloroform) it was separated from the mixture and subjected to spectrophotometric analysis in the UV region (279 nm). The stability of the standard solution of furfural and waste disposal were evaluated. The viability of the LLE method was evaluated in the determination of furfural in samples of sugar cane spirits. The proposed method was compared with the reference method based on gas chromatography with flame ionization detector (FID) (GC-FID), no statistical difference between the results was observed. The LLE method was sensitive, accurate and precise with recoveries in the range 102-109%, linear range of 0,2 to 8 mg 100 ml-1, limits of detection and quantification of 0,0118 mg 100 mL-1 and 0,0203 mg 100 ml-1, respectively, repeatability factor of 0,026. The LLE methodology was validated and successfully applied to the analysis of eight cachaças samples demonstrating the feasibility and reliability of the method. The levels of furfural, in the analyzed cachaças was between 0,4 to 1,1 mg 100 mL-1 and is therefore, beverages analyzed, within the limit of 5 mg 100 mL-1, established by legislation.